Intertemporal Bargaining in Addiction - Ainslie, George (Frontiers in Psychiatry, 2013)
The debate between disease models of addiction and moral or voluntarist models has been endless, and often echoes the equally endless debate between determinism and free will. I suggest here that part of the problem comes from how we picture the function of motivation in self-control. Quantitative experiments in both humans and nonhumans have shown that delayed reward loses its effectiveness in proportion to its delay. The resulting instability of preference is best controlled by a recursive self-prediction process, intertemporal bargaining, which is the likely mechanism of both the strength and the experienced freedom of will. In this model determinism is consistent with more elements of free will than compatibilist philosophers have heretofore proposed, and personal responsibility is an inseparable, functional component of will. Judgments of social responsibility can be described as projections of personal responsibility, but normative responsibility in addiction is elusive. The cited publications that are under the author’s control can be downloaded from www.picoeconomics.org.